Comprehensive analysis of host cell impurities in monoclonal antibodies with improved sensitivity by capillary zone electrophoresis mass spectrometry. Issue 3 (14th December 2016) - Zhang, Zhenbin; Albanetti, Thomas; Linkous, Travis; Larkin, Christopher J.; Schoner, Ronald; McGivney, James B.; Dovichi, Norman J
Abstract : Four methods were compared for analysis of host‐cell protein (HCP) impurities in a recombinant mAb. First, CZE‐MS/MS was used to analyze the digest of an HCP sample following extraction of the mAb with proteins A and L affinity columns; 220 protein groups and 976 peptides were identified from the depleted HCP digest. Second, a nanoACQUITY UltraPerformance LCH system was also used to analyze the depleted HCP digest; 34 protein groups and 53 peptides from 50 ng of the depleted HCP digest and 290 protein groups and 1011 peptides were identified from 1 μg of the depleted HCP digest. Third, 185 protein groups and 709 peptides were identified by CZE‐MS/MS from the HCP digest without depletion. Fourth, a strong cation exchange SPE was coupled to CZE‐ESI‐MS/MS using online pH gradient elution for analysis of the HCP digest without depletion. A series of five pH bumps were applied to elute peptides from the strong cation exchange monolith followed by analysis using CZE coupled to a Q Exactive HF mass spectrometer; 230 protein groups and 796 peptides were identified from the HCP digest without depletion.